Consumers' Omnichannel Integration Quality, Credibility and Innovativeness Perceptions of the Brands and Omnichannel Adoptions - Mazan, Ilknur; CETINEL, M. Hurmet; Onaran, Berrin (International Journal of Contemporary Economics and Administrative Sciences, 2024)
In this study it is aimed to reveal how brands' omnichannel integration quality, omnichannel credibility and perceived innovativeness influence consumers’ omnichannel adoption and to reveal the mediating role of perceived omnichannel value on this effect. Also, it examines the omnichannel usage in tourism, banking, clothing and furniture sectors. For this purpose, the data obtained by sending an online questionnaire via social media applications and via email to 411 people from different cities and having different demographic characteristics were analyzed by SEM method. According to the results of the analysis, a relationship was found between omnichannel integration quality, omnichannel credibility and perceived brand innovativeness. In addition, it was concluded that perceived omnichannel value has a mediating role in the effect of omnichannel credibility and brand innovativeness variables on the omnichannel adoption variable, while it does not have a mediating role in the effect of the omnichannel integration quality variable on the omnichannel adoption variable. It is thought that this study and the results obtained are important in terms of being a guide in theory and practice, since the variables in the study are related to the use of omnichannel in the product and service purchasing processes of consumers.